Insights into the Regulatory Roles of miRNAs in the Salivary Glands of the Soft Ticks Ornithodoros moubata and Ornithodoros erraticus - Ana Laura Cano-Argüelles; Ricardo Pérez-Sánchez; Cristian Gallardo-Escárate; Rocío Vizcaíno-Marín; María González-Sánchez; Ana Oleaga (Pathogens)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression by inhibiting or degrading messenger RNAs (mRNAs). In ticks, salivary miRNAs are proposed to play key roles in modulating host–vector interactions during blood feeding. Previously, we identified salivary miRNAs in Ornithodoros moubata and Ornithodoros erraticus, major vectors of African swine fever and tick-borne human relapsing fever. In this study, we investigated the regulatory roles of salivary miRNAs in tick biology. Salivary miRNA datasets were re-analysed to identify conserved miRNAs, and putative target genes were predicted using the sialotranscriptomes of both species. In silico predictions were validated through experimental inhibition of specific miRNAs using antagomirs. Knockdown of miR-375 and miR-1 significantly reduced blood intake, oviposition, and fertility, indicating their involvement in feeding and reproductive processes. Silencing miR-252b in O. moubata led to increased mortality, suggesting a critical role in survival. Notably, Metis1 was identified as a likely target of miR-252b, and its dysregulation may underlie the observed lethality in miR-252b-silenced ticks. These findings highlight the functional relevance of salivary miRNAs in tick physiology and host interaction, offering new perspectives for the development of innovative tick control strategies.